2024
DOI: 10.1039/d3tb03014h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the induction heating efficacy of sol–gel derived SiO2–CaO–Na2O–P2O5 bioglass-ceramics by incorporating magnetite nanoparticles

Nitu,
Rushikesh Fopase,
Lalit Mohan Pandey
et al.

Abstract: Magnetite (Fe3O4) nanoparticle (MNP) substituted glass-ceramic (MSGC) powders with compositions of (45-x)SiO2-24.5CaO-24.5Na2O-6P2O5-xFe3O4 (x = 5, 8, and 10 wt. %) have been prepared by sol-gel route by introducing Fe3O4 nanoparticles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…It can be observed that some researchers have solely focused on magnetic properties, while a few others have extensively investigated bioactivity and heating capacity of these ceramics. One can also notice that except [3,6]., all the studied compositions deviated from the Hench composition.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…It can be observed that some researchers have solely focused on magnetic properties, while a few others have extensively investigated bioactivity and heating capacity of these ceramics. One can also notice that except [3,6]., all the studied compositions deviated from the Hench composition.…”
Section: Introductionmentioning
confidence: 75%
“…At T A > 550 • C, conversion of magnetite into hematite could be noticed along with further reduction in NaNO 3 phase [6]. Since, the presence of hematite degrades the magnetic properties, the optimum T A appears to be 550 • C. It may also be noted that combeite does not impede the formation of hydroxyapatite layer (HAp) under physiological conditions, and hence the bioactivity of the sample remains unaffected [20].…”
Section: Resultsmentioning
confidence: 99%
“…Higher SAR indicates increased power absorption by the material and, hence, an improved heating efficiency. SAR can be estimated by employing the initial slope method (ISM) and the Box Lucas method (BLM) techniques. , The BLM technique takes into account the entire heating curve, while the ISM method focuses on only the initial slope. Therefore, the latter is considered to be more relevant for this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the latter is considered to be more relevant for this investigation. The increase in temperature (Δ T ) was estimated using eq , normalΔ T = A ( 1 e ( B Δ T ) ) In the above expression, A and B represent the fitting parameters. Then, the SAR was computed by employing eq SAR = italicAB C v m i m Np In eq , m Np , m i , and C v represent the mass of MGCC powder, the entire mass of the magnetic fluid, and the specific heat capacity of the aqueous solvent, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation